Remote Ischemic Preconditioning to Prevent Acute Kidney Injury After Cardiac Surgery: A Meta-Analysis of Randomized Controlled Trials - Liu, Zigang; Zhao, Yongmei; Lei, Ming; Zhao, Guancong; Li, Dongcheng; Sun, Rong; Liu, Xian (Frontiers in Cardiovascular Medicine, 2021)
Objective: Randomized controlled trials (RCTs) evaluating the influence of remote ischemic preconditioning (RIPC) on acute kidney injury (AKI) after cardiac surgery showed inconsistent results. We performed a meta-analysis to evaluate the efficacy of RIPC on AKI after cardiac surgery. Methods: Relevant studies were obtained by search of PubMed, Embase, and Cochrane’s Library databases. A random-effect model was used to pool the results. Meta-regression and subgroup analyses were used to determine the source of heterogeneity. Results: Twenty-two RCTs with 5,389 patients who received cardiac surgery – 2,702 patients in the RIPC group and 2,687 patients in the control group - were included. Moderate heterogeneity was detected (p for Cochrane’s Q test = 0.03, I2 = 40%). Pooled results showed that RIPC significantly reduced the incidence of AKI compared to control (odds ratio [OR]: 0.76, 95% confidence intervals [CI]: 0.61~0.94, p = 0.01). Results limited to on-pump surgery (OR: 0.78, 95% CI: 0.64~0.95, p = 0.01) or studies with acute RIPC (OR: 0.78, 95% CI: 0.63~0.97, p = 0.03) showed consistent results. Meta-regression and subgroup analyses indicated that study characteristics, including study design, country, age, gender, diabetic status, surgery type, use of propofol or volatile anesthetics, cross-clamp time, RIPC protocol, definition of AKI, and sample size did not significantly affect the outcome of AKI. Results of stratified analysis showed that RIPC significantly reduced the risk of mild-to-moderate AKI that did not require renal replace therapy (RRT, OR: 0.76, 95% CI: 0.60~0.96, p = 0.02), but did not significantly reduce the risk of severe AKI that required RRT in patients after cardiac surgery (OR: 0.73, 95% CI: 0.50~1.07, p = 0.11). Conclusions: Current evidence supports RIPC as an effective strategy to prevent AKI after cardiac surgery, which seems to be mainly driven by the reduced mild-to-moderate AKI events that did not require RRT. Efforts are needed to determine the influences of patient characteristics, procedure, perioperative drugs, and RIPC protocol on the outcome.